2022
DOI: 10.1099/ijsem.0.005214
|View full text |Cite
|
Sign up to set email alerts
|

Rhodothermus bifroesti sp. nov., a thermophilic bacterium isolated from the basaltic subsurface of the volcanic island Surtsey

Abstract: Novel thermophilic heterotrophic bacteria were isolated from the subsurface of the volcanic island Surtsey off the south coast of Iceland. The strains were isolated from tephra core and borehole fluid samples collected below 70 m depth. The Gram-negative bacteria were rod-shaped (0.3–0.4 µm wide, 1.5–7 µm long), aerobic, non-sporulating and non-motile. Optimal growth was observed at 70 °C, at pH 7–7.5 and with 1% NaCl. Phylogenetic analysis identified the strains as members of the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Most of the isolates were aerobic and heterotrophic bacteria, and few novel species were isolated. In this perspective, a bacterium isolated in this study, Rhodothermus bifroesti, has been characterized [56]. The comparison of our cultured strains and ASVs from 16S rRNA amplicon gene datasets obtained from the same samples [37] revealed that isolates were detected using both culture-dependent (isolation) and -independent methods (metabarcoding).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Most of the isolates were aerobic and heterotrophic bacteria, and few novel species were isolated. In this perspective, a bacterium isolated in this study, Rhodothermus bifroesti, has been characterized [56]. The comparison of our cultured strains and ASVs from 16S rRNA amplicon gene datasets obtained from the same samples [37] revealed that isolates were detected using both culture-dependent (isolation) and -independent methods (metabarcoding).…”
Section: Discussionmentioning
confidence: 91%
“…The closest neighbor sequences corresponded to uncultured Rhodothermus species detected in seawater (EU249949) and Rubrobacter xylanophilus DSM 9941 isolated from hot spring water samples (CP000386) (Figure 2). The novel strains of Rhodothermus were characterized, and the name Rhodothermus bifroesti was attributed to the new species [56]. In addition, other isolated strains potentially represent novel species.…”
Section: Phylogeny Of the Isolates And Habitat Of The Closest Relativesmentioning
confidence: 99%
“…One example of these underexplored extreme environments is deep subsurface geothermal reservoirs used either for heating or for electricity production. Microbial strains isolated from these deep subsurface geothermal fluids include diverse bacterial species such as Thermus thermophilus TMY [16], Anoxybacillus geothermalis [17], [18], and Rhodothermus bifroesti [19], and archaeal strains including Pyrobacurum [20] or Archaeoglobus fulgidus [21]. However, to the best of our knowledge, no fungi had yet been isolated from deep geothermal fluids.…”
Section: Introductionmentioning
confidence: 99%